A 24-month updated analysis of the comparative effectiveness of ZUMA-5 (axi-cel) vs. SCHOLAR-5 external control in relapsed/refractory follicular lymphoma. Issue 2 (1st February 2023) - Palomba, M Lia; Ghione, Paola; Patel, Anik R; Nahas, Myrna; Beygi, Sara; Hatswell, Anthony J; Kanters, Steve; Limbrick-Oldfield, Eve H.; Wade, Sally W; Ray, Markqayne D; Owen, Jessica; Neelapu, Sattva S; et al.
ABSTRACT: Background: In the ZUMA-5 trial (Clinical trials identification: NCT03105336), axicabtagene ciloleucel (axi-cel; a chimeric antigen receptor T-cell therapy) demonstrated high rates of durable response in relapsed/refractory (r/r) follicular lymphoma (FL) patients and clear superiority relative to the SCHOLAR-5 external control cohort. We update this comparison using the ZUMA-5 24-month data. Research design and methods: The SCHOLAR-5 cohort is comprised of r/r FL patients who initiated ≥3 rd line of therapy after July 2014 and meeting ZUMA-5 eligibility criteria. Groups were balanced for patient characteristics through propensity scoring on prespecified prognostic factors using standardized mortality ratio (SMR) weighting. The overall response rate was compared using a weighted logistic regression. Time-to-event outcomes were evaluated using a Cox regression. Results: For SCHOLAR-5, the sum of weights for the 143 patients was 85 after SMR weighting, versus 86 patients in ZUMA-5. The median follow-up was 29.4 months and 25.4 months for ZUMA-5 and SCHOLAR-5, respectively. The hazard ratios for overall survival and progression-free survival were 0.52 (95% confidence interval (CI): 0.28–0.95) and 0.28 (95% CI: 0.17–0.45), favoring axi-cel. Conclusion: This updated analysis, using a longer minimum follow-up than a previously published analysis, shows that the improved efficacy of axi-cel, relative to available therapies, in r/r FL is durable. .